Historically recontextualizing Sidman's Tactics: How behavior analysis avoided psychology's methodological Ouroboros. Issue 1 (17th December 2020) - Imam, Abdulrazaq A.
Abstract : Psychology is undergoing major cultural changes methodologically, with efforts to redefine how psychologists analyze and report their data. Davidson (2018) argued that psychology's methodological crises stem from mechanical objectivity involving the adoption of an analytic tool as source of dependable knowledge. This has led to institutionalization, and eventually uncritical ritualistic use, such as happened with null hypothesis statistical testing. Davidson invoked the mythological symbol of the Ouroboros to represent the endless churning of statistical fads. Sidman (1960), in his Tactics of Scientific Research provided a shield from these problems in terms of the premium he placed on the experience, expertise, judgement, and decision‐making of the scientist, that appear to be absent in psychology's ritualized processes.